2022
DOI: 10.1038/s41557-022-01021-z
|View full text |Cite
|
Sign up to set email alerts
|

A modular XNAzyme cleaves long, structured RNAs under physiological conditions and enables allele-specific gene silencing

Abstract: Nucleic acid catalysts (ribozymes, DNA- and XNAzymes) cleave target (m)RNAs with high specificity but have shown limited efficacy in clinical application. Here we report on the in vitro evolution and engineering of a highly specific modular RNA endonuclease XNAzyme, FR6_1, composed of 2’-deoxy-2’-fluoro-β-D-arabino nucleic acid (FANA). FR6_1 overcomes activity limitations of previous DNA- and XNAzymes and can be retargeted to cleave highly structured full-length (>5 kb) BRAF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 86 publications
1
56
0
Order By: Relevance
“…Next, we sought to combine SARS-CoV-2 XNAzymes in order to target the genome synergistically and to stabilise catalysts prior to examining activity in vivo. Previously, we found that a cocktail of three FR6_1derived XNAzymes was able to cleave a long, structured RNA target at expected sites without mutual interference 31 . However, as FANA displays only modest resistance to serum exonucleases, further modifications (FANA phosphorothioate linkages) had to be introduced to improve biostability.…”
Section: Synthesis Of a Catalytic Xna Nanostructurementioning
confidence: 99%
See 4 more Smart Citations
“…Next, we sought to combine SARS-CoV-2 XNAzymes in order to target the genome synergistically and to stabilise catalysts prior to examining activity in vivo. Previously, we found that a cocktail of three FR6_1derived XNAzymes was able to cleave a long, structured RNA target at expected sites without mutual interference 31 . However, as FANA displays only modest resistance to serum exonucleases, further modifications (FANA phosphorothioate linkages) had to be introduced to improve biostability.…”
Section: Synthesis Of a Catalytic Xna Nanostructurementioning
confidence: 99%
“…The modular RNA endonuclease XNAzyme FR6_1 was initially selected to cleave an RNA sequence in the genome of Zaire Ebolavirus ('Sub_-Ebo') and is predicted to have an architecture comprised of a catalytic core flanked by two guide strands or substrate-binding 'arms' 31 . Substrate specificity arises from a combination of the complementarity of the binding arms for target RNA, as well as putatively unpaired substrate residues positioned in a three-residue bulge opposite the catalytic core-although FR6_1 tolerates almost any dinucleotide pair (except GG) at the cleavage site in this bulge, there is an absolute requirement for an A one nucleotide downstream 31 . Initially, we searched the RNA genome of SARS-CoV-2 (NCBI NC_045512.2) for sequences with similarity to the original target sequence of FR6_1, but with no similar (i.e.…”
Section: Engineering Xnazymes To Target Sars-cov-2 Rnamentioning
confidence: 99%
See 3 more Smart Citations